SEKOLAH RAMAH ANAK BERBASIS HAK ANAK DI SEKOLAH DASAR - Ambarsari, Luthfiana; Harun, Harun (Universitas Muhammadiyah Surakarta, 2018)
Abstrak: This research aimed to describe the child-friendly school policy in two child-friendly pilot primary schools. This research concern: â€œHow does the implementation of child-friendly school policy based child rights at primary school?â€ The method that used in this research was a qualitative type of phenomenology. The data were collected by observation method, interview, and documentation. The data analysis technique that used was phenomenology research data analysis of Burke Johnson and Larry Christensen. The results showed that there were 3 discoveries related to child-friendly school policies in primary schools. First, the child-friendly school policies were designed and implemented to ensure children's rights were fulfilled. Second, the child-friendly school policies were implemented in learning area, the school social environments, the schoolâ€™s physical environment, and infrastructure facilities. Third, the child-friendly school policies were applied to create condition conducive and fun in school.